Introduction: Forced Migration and Protracted Transit in Indonesia and Southeast Asia - Danau Tanu; Antje Missbach; Dave Lumenta (Antropologi Indonesia, 2017)
In May 2015, boats carrying several thousand Rohingya refugees created a tense situation in the region as Indonesia and neighboring ASEAN countries initially refused to let them come ashore (Amnesty International, 2015). Refugees dominated regional headlines for weeks for the first time since the end of the Vietnam war in 1975, when Indonesia and many other Southeast Asian states saw the arrival of tens of thousands of people from Vietnam and then later from Cambodia. The public outcry at the time led to a strong support for finding a regional solution for refugees. Despite this, the protection of asylum seekers and refugees across Southeast Asia remains weak to this day (Gleeson, this issue; Tan, 2016). Although Southeast Asia currently hosts more than one million4 asylum seekers and refugees (Amnesty International, 2017; UNHCR, 2017b), most Southeast Asian countries, with the exception of Cambodia, Timor Leste and the Philippines, have not signed the 1951 Refugee Convention and do not offer local integration for refugees in their respective territories.